Feminism after Postmodernism : Theorising through Practice. (Taylor & Francis, 2000)
This book provides a detailed overview of postmodern feminist theory and practice. The author critically examines the work of the major contemporary feminist theorists and makes a significant intervention into current debates about the future of feminism. Subjects covered include: the differences between the feminism of the 1970s and contemporary feminism liberal, radical, socialist and postmodern feminisms feminist reactions to the growth in reproductive technologies how feminism informs debates about the subject, epistemology and political action feminism into the new millennium Highly original and stimulating, this book is essential reading for all those interested in gender studies and feminist theory.